Should all adult cystic fibrosis patients with repeated nontuberculous mycobacteria cultures receive specific treatment? A 10-year case–control study. Issue 5 (4th February 2016) - Albrecht, Christiane; Ringshausen, Felix; Ott, Sebastian; Wagner, Dirk; Rademacher, Jessica; Schneider, Michael; Welte, Tobias; Pletz, Mathias W.
The disease caused by nontuberculous mycobacteria (NTM) forms a broad clinical spectrum from asymptomatic infection to fatal disseminated disease in humans. While many NTM patients have underlying pulmonary diseases, NTM symptoms are undifferentiated from symptoms of patients with chronic pulmonary structural diseases [1]. Not all CF patients with MAC detected in respiratory samples require anti-mycobacterial treatment http://ow.ly/X66gt